2021
DOI: 10.3389/fonc.2020.566804
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic Alterations in Multiple Myeloma: A Comprehensive Study Using Bone Marrow Interstitial Fluid and Serum Samples

Abstract: Multiple myeloma (MM) is a plasma cell-associated cancer and exists as the second most common hematological malignancy worldwide. Although researchers have been working on MM, a comprehensive quantitative Bone Marrow Interstitial Fluid (BMIF) and serum proteomic analysis from the same patients’ samples is not yet reported. The present study involves the investigation of alterations in the BMIF and serum proteome of MM patients compared to controls using multipronged quantitative proteomic approaches viz., 2D-D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 82 publications
1
13
0
Order By: Relevance
“…Jinfang Xu et al found the forced expression of Kininogen-1 represses the glioma cells proliferation and promotes apoptosis 41 . Proteomic data showed the Kininogen 1 is closely related to the development of MM 42 . GPCR and RGS signaling pathways play key roles in maintaining the cell functions and metabolisms [43][44][45][46] .…”
Section: Discussionmentioning
confidence: 99%
“…Jinfang Xu et al found the forced expression of Kininogen-1 represses the glioma cells proliferation and promotes apoptosis 41 . Proteomic data showed the Kininogen 1 is closely related to the development of MM 42 . GPCR and RGS signaling pathways play key roles in maintaining the cell functions and metabolisms [43][44][45][46] .…”
Section: Discussionmentioning
confidence: 99%
“…Serum concentrations of S100A8 and LRG1 were measured using human S100A8 and LRG1 ELISA assay kits (Uscn, China), respectively. ELISAs were performed as previously described ( 12 ) according to manufacturer’s instructions. The absorbance values of the standards and samples were determined by spectrophotometry at 450 nm using a microplate reader.…”
Section: Methodsmentioning
confidence: 99%
“…Deregulation of protein expression was reported in MM patients compared to non-malignant samples, demonstrating their diagnostic and/or prognostic potentials. Several studies showed a differential expression of various proteins such as haptoglobin, kininogen 1, transferrin, serum amyloid A protein, plasma kallikrein, integrin alpha-11, apolipoprotein A-I, sulfhydryl oxidase 1 and isoform-1 of multimerin-1 in the sera of MM patients [ 128 , 129 , 130 ].…”
Section: Novel Biomarkers For Diagnosis and Prognosis Of MMmentioning
confidence: 99%